Lamotrigine Overdose: A Case Report - Rahman, Shafiq Ur; Uzma Akhtar; Waheed Ullah (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
Lamotrigine is a second-generation anticonvulsant and mood stabilizer commonly used to treat epilepsy and bipolar disorder. Although generally well tolerated, overdoses can cause significant toxicity affecting the central nervous and cardiovascular systems. We report a case of a 34-year-old female with conversion disorder who ingested 1000 mg of lamotrigine following an emotional distress episode. She presented with slurred speech, tachycardia, and lethargy but remained hemodynamically stable. Management included gastric lavage, activated charcoal, and supportive care, resulting in a favorable outcome without complications. This case highlights the importance of early intervention in lamotrigine toxicity and the need for psychiatric evaluation in at-risk patients.